Opłaty służące ochronie środowiska a ekologiczne fundusze celowe w Polsce - Ptak, Michał (Environmentally related charges and earmarked environmental funds in Poland, 2008)
The paper presents the advantages and disadvantages of earmarking the revenue from environmentally related charges for financing environmental projects. This earmarking may have a form of public environmental funds. Particular attention is paid to the Polish Funds for Environmental Protection and Water Management which are important parts of the integrated system of financing environmental protection in Poland. The author also presents the role of subfunds existing in the National Fund For Environmental Protection and Water Management.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 92-105